In Vivo Absolute Metabolite Quantification Using a Multiplexed ERETIC‐RX Array Coil for Whole‐Brain MR Spectroscopic Imaging. Issue 1 (11th June 2022) - Thapa, Bijaya; Mareyam, Azma; Stockmann, Jason; Strasser, Bernhard; Keil, Boris; Hoecht, Philipp; Carp, Stefan A.; Li, Xianqi; Wang, Zhe; Chang, Yulin V.; Dietrich, Jorg; Uhlmann, Erik; et al.
Abstract : Absolute concentration maps in mM unit of glutamine plus glutamate (GLX) and myo‐inositol (MI) in the five healthy subjects obtained from ERQ and IWQ methods. The corresponding high‐resolution MEMPRAGE image and CSF segmentation map down‐sampled to MRSI size are shown in the first and second columns, respectively BY Bijaya Thapa et al. (121‐133)